Morinda officinalis iridoid glycosides, as an inhibitor of GSK-3β, alleviates rheumatoid arthritis through inhibition of NF-κB and JAK2/STAT3 pathway - Shen, Yi; Bao, Ronghua; Ye, Xinyuan; Li, Heming; Sun, Yiqi; Ren, Qiuru; Du, Jinman; Ye, Tianwen; Zhang, Quanlong; Zhao, Qiming; Han, Ting; Qin, Luping; et al. (Frontiers in Pharmacology, 2024)
Background Morinda officinalis iridoid glycosides (MOIG) showed potential benefits in the treatment of rheumatoid arthritis (RA), but their exact mechanism has yet to be explored. Purpose To evaluate the effects of MOIG on RA, and explore the potential targets and molecular mechanism of MOIG in RA. Methods The collagen-induced arthritis (CIA) rats were used to evaluate the effects of MOIG on RA. The proliferation, migration and invasion of fibroblast-like synoviocytes (FLSs) stimulated with or without tumor necrosis factor (TNF)-α were examined by CCK-8, wound healing and transwell assays, respectively. IF and WB were applied to investigate related mechanism in FLSs. The molecular docking, molecular dynamics simulation, CETSA and siRNA were used to analyze the interaction of MOIG with target. Finally, the adjuvant-induced arthritis (AA) mice model with gene knockdown was used to confirm the effect of MOIG on glycogen synthase kinase-3β (GSK-3β). Results MOIG significantly alleviated the paw swelling and synovial hyperplasia in CIA rats. Moreover, MOIG suppressed proliferation, migration and invasion, the secretion of inflammatory factors, and the expression of adhesion related proteins in TNF-α-stimulated FLSs. MOIG also inhibited the activation of Janus activating kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) and nuclear factor kappa-B (NF-κB) signaling pathway in FLSs. Interestingly, the plant metabolites in MOIG had a good affinity with GSK-3β, and inhibition of GSK-3β attenuated the effects of MOIG on FLSs. Knockdown GSK-3β gene could inhibit the paw swelling and inflammatory indicators, decrease the arthritis score and synovial hyperplasia, reduce the phosphorylation of p65 and STAT3 in AA mice, thereby suppressing the NF-κB and STAT3 signaling activation, and MOIG treatment had no significant effects on AA mice with si-GSK-3β. Conclusion MOIG alleviates joint inflammation in RA through inhibition NF-κB and JAK2/STAT3 pathway via suppression of GSK-3β in FLSs, which provides supports for MOIG as a promising therapeutic agent of RA.